Soft-Sediment Structures in Mud-Dominated Turbidites of Pedawan Formation (Upper Jurassic - Cretaceous) along Jambusan-Semadang Road, Siburan, Sarawak, Malaysia - Samsudin, N.M. (Slovnaft VURUP a.s, 2021)
Three (3) outcrops belonging to the Pedawan Formation found along Jambusan-Semadang Road in the Siburan area are characterized by well-developed soft-sediment deformation structures (SSDS). SSSD is formed due to instability, which possibly results from factors like rapid sedimentation, overloading, or earthquake. The SSDS in Siburan, in the form of folded and faulted structures, were recorded within thick sequences of mud-dominated turbidites of the Pedawan Formation (Jurassic - Cretaceous age). These SSDS are grouped into five (5) different types, which are 1) mud-dominated slumped structures, 2) folded and overturned sandstone beds, 3) contorted argillaceous mudstone beds, 4) sandstone boulder, and 5) envelope structure. The small-scale SSDS (<1 m), like localized slumps and envelope structure, are interpreted to have formed due to overloading and rapid deposition. The large SSDS (> 1 m), such as detached sandstone blocks, internal faulting, and folds, are attributed to movements related to earthquakes. Â© 2021. All Rights Reserved.